A novel conversion strategy for organic compounds in waste liquid crystal displays based on the near/supercritical methanol process. (November 2022) - Xiu, Fu-Rong; Song, Zhiqi; Lu, Yongwei; Qi, Yingying; Wang, Mengmeng
Graphical abstract: Highlights: We report an efficient near/supercritical methanol process for treatment of waste LCD. Conversion ratio of the organic compounds could reach 98% at 300 °C. TPP, PVA and LC were mainly converted or recovered at a temperature below 200 °C. CTA was converted at a temperature above 300 °C. High value-added chemicals were obtained from waste LCD by the NSCM process. Abstract: Waste liquid crystal displays (LCD) contain a large number of organic compounds such as cellulose triacetate (CTA), poly(vinyl alcohol) (PVA), triphenyl phosphate (TPP), and liquid crystal (LC). It is important to recover organic compounds from waste LCD due to their value and environmental toxicity. However, it is challenging to recover organic compounds from waste LCD because of the heterogeneous mixture of glass, organics and metals contained therein. In this study, an environment-friendly near/supercritical methanol (NSCM) process was developed as a closed cycle technology for the conversion of organic compounds from waste LCD. The acid-base catalytic activity and nonpolar property of the NSCM could efficiently promote the conversion of organic compounds from waste LCD. TPP could be extracted below 200 °C in the NSCM process. Below 250 °C, the conversion ratio of organic compounds from waste LCD ranged from 5 % to 68 % due to the extraction or decomposition of TPP, LC, and PVA. The main products obtained at 250 °C included long-chain alcohols and alkanes with a similar composition to industrial liquid paraffin, which could be widely used in other industrial processes. Under the optimal operation parameters (300 °C, 30 min, and 1:20 g/ml), the conversion ratio of organic compounds could reach 98 % due to the efficient decomposition of CTA. The main products obtained included ketones and esters chemicals, which could be further used as a chemical feedstock. No secondary pollutant was generated in the whole process. The low-boiling methanol could easily be recycled, which could make the NSCM a clean process for the production of high value-added organic products from waste LCD.